Top-of-the-Line Corrosion in The Presence of Hydrocarbon Co-Condensation in Flowing Condition - Pojtanabuntoeng, Thunyaluk; Singer, M.; Nesic, S. (Curran Associates, 2012)
During the transportation of wet gas, temperature gradient between the internals of the pipeline and the outside environment leads to the condensation of water vapor. Freshly condensed water is very corrosive and can lead to the so-called Top-of-the-Line Corrosion (TLC). However, a certain fraction of hydrocarbons will co-condense along with the water vapor resulting in two immiscible liquids at the pipe wall with a different wettability and different corrosivity. To elucidate the role of co-condensation, corrosion tests in the absence and presence of hydrocarbon were conducted. In the experiments, hot vapors of water and n-heptane saturated with CO2 were generated and transported through a one-inch internal diameter condenser tube, with 2 carbon steel samples located at the inlet and outlet of the tube. Condensation took place on the inner surface of the tube and was related to the TLC. Corrosion rate was evaluated by the weight loss method. In the absence of co-condensation, corrosion rates increased with water condensation rates. In the presence of n-heptane co-condensation, water condensation rates had less influence on the corrosion rates. Iron carbonate (FeCO3) was observed only in the co-condensation scenario, suggesting the change of the chemistry of condensed water